A chitosan-graft-PEI-eprosartan conjugate for cardiomyocyte-targeted VEGF plasmid delivery in myocardial ischemia gene therapy. Issue 2 (22nd January 2016) - Yu, Ke; Wu, Suhua; Li, Hong
Abstract : A multifunctional copolymer conjugate chitosan-graft-polyethyleneimine-eprosartan (CPE) containing low-molecular-weight chitosan backbone and polyethyleneimine (PEI) arms with eprosartan (ES) conjugated via an amide bond was fabricated as a cardiomyocyte-targeted vascular endothelial growth factor (VEGF) plasmid delivery nanovector. Here, ES was utilised to specifically bind to overexpressed angiotensin II type 1 receptor (AT1 R) of cardiomyocytes and strengthen endosomal buffering capacity of CPE. The self-assembled CPE/VEGF complexes exhibited desirable and homogenous particle size, moderate positive charges, advanced gene condensation and protection profiles in vitro . Flow cytometry and ELISA analyses confirmed that ES-targeted function and ES-enhanced buffering capacity induced specific cellular uptake and high transfection of CPE/VEGF complexes in AT1 R-overexpressed H9C2 cells. In vivo investigation on myocardial ischemia rat model revealed that CPE/VEGF complexes possessed strong therapeutic effect. These findings suggested that CPE could be an ideal cardiomyocyte-targeted nanovector for effective transfer of VEGF plasmid, and a multifunctional CPE/VEGF delivery system with cardiomyocyte-specific targetability, enhanced endosomal buffering capacity and strong therapeutic effect might be a new promising strategy for effective myocardial ischemia gene therapy.